Pengaruh Gaya Kepemimpinan dan Komunikasi Organisasi Terhadap Kepuasaan Kerja Pada BP3IP Jakarta - Atria Maharani; Ratna Kurnia Dewi (Majalah Ilmiah Bahari Jogja, 2021)
The purpose of this study was to determine how much was the influence of the leadership style and organizational communication on BP3IP Jakarta toward its officers’ performance satisfaction. The data collection method used by the researchers was through primary and secondary data obtained from interviews and observations in BP3IP Jakarta office environment. From the results of the discussion found that: 1) the leadership style had a positive and significant impact on the institution job satisfaction, 2) the implementation of organizational communication still required further attention from the institution, even though in general the implementation of organizational communication had gone well. However, by looking at the situation, it needed to broaden the organizational communication level, because this could provide comforts and freedoms in developing the officers’ creativity, and evaluation because of the professional organization communication assessment.